Pandangan Hamka Tentang Nilai Pancasila dalam al-Qur’an - Zainul Ma'ruf; Kayyis Fitrhi Ajhuri (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2024)
Pancasila is the basic ideology and philosophy of the Indonesian nation. Pancasila is created by the Indonesian people themselves because the values”‹contained in each of the Pancasila principles come from the customs and culture of Indonesian society. However, in this modern era, Islamic dynamics in Indonesia always become lively when there is a debate discussing the clash between two aspects, namely Islam and Pancasila. By using a descriptive-analytical approach, the results of this research were obtained as follows: 1. According to Buya Hamka, the main essence of Pancasila lies in the principle of Belief in One Almighty God. Buya Hamka said that by adhering to the precepts of Belief in One Almighty God, you will automatically grow and practice the other four precepts. The first principle talks about monotheism in accordance with Surah al-Iá¸¥lÄá¹£ verses 1-4. The second principle talks about humanity in accordance with Surah al-Baqara; verse 83. The third precept talks about national unity in accordance with surah al-HujurÄt verse 13. The fourth precept talks about the obligation of the people to consult in accordance with surah ash-ShÅ«ra verse 38. The fifth precept talks about social justice in accordance with surah an-NisÄ' verse 36. 2. In the Tafsir Al-Azhar book, surah al-Iá¸¥lÄá¹£ verses 1-4 which contain the value of the Oneness of God. Surah al-Baqara; verse 83 Buya Hamka interprets that this verse contains human attitudes which are a reflection of human attitudes.